Epistemologi Harmonisasi Ilmu dalam Transformasi Kelembagaan UIN K.H. Abdurrahman Wahid Pekalongan - Hibrizi, Azzam Nabil; Saffanah, Syafika (PT PUBLIKASI INSPIRASI INDONESIA, 2025)
The relations between science and religion often lead to conflict. Harmonization of religion and science is present here to reduce these conflicts. This harmonization is also needed in the scope of education, especially in Islamic educational institutions, such as Islamic religious universities. One of the PTKI that implements science-based science and religion harmonization is UIN KH Abdurrahman Wahid Pekalongan, using science harmonization as its scientific philosophical framework. This analysis of how the implementation of science and religion harmonization-based science at UIN K.H. Abdurrahman Wahid Pekalongan uses qualitative research methods, descriptive approaches, through literature studies in collecting information relevant to the theme of discussion and using an ontological-historical perspective. The outcome of this research is that, from the ontological point of view, the scientific philosophy of science harmonization uses tawhid as its scientific basis. While in its historical perspective, this can be viewed from the development of the university to form a new scientific design based on the harmonization religion and science. The implementation at UIN K.H. Abdurrahman Wahid Pekalongan of the harmonization between religion and science is apparent from the harmonization of science in the courses and study programs provided by the university.